Predictors for Therapy Response to Intrathecal Corticosteroid Therapy in Multiple Sclerosis - Vohl, Katja; Duscha, Alexander; Gisevius, Barbara; Kaisler, Johannes; Gold, Ralf; Haghikia, Aiden (Frontiers in Neurology, 2019)
Objective The autoimmune disease Multiple Sclerosis (MS) represents a heterogeneous disease pattern with an individual course that may lead to permanent disability. In addition to immuno-modulating therapies patients benefit from symptomatic approaches like intrathecal corticosteroid therapy (ICT), which is frequently applied in a growing number of centers in Germany. ICT reduces spasticity, which elongates patient’s walking distance and speed, thus improves quality of life. Methods In our study we set out to investigate cerebrospinal fluid (CSF) parameters and clinical predictors for response to ICT. Therefore, we analyzed 811 CSF samples collected from 354 patients over a time period of 12 years. Patients who received ICT were divided in two groups (improving or active group) depending on their EDSS-progress. As control groups we analyzed data of ICT naïve patients, who were divided in the two groups as well. Additionally we observed the clinical progress after receiving ICT by comparison of patients in both groups. Results The results showed clinical data had a significant influence on the probability to benefit from ICT. The probability (shown by Odds Ratio of 1.77 to 2.43) to belong to the improving group in contrast to the active group is significantly (p < 0.0001) higher at later stages of disease with early disease onset (<35 years, OR=2.43) and higher EDSS at timepoint of ICT-initiation (EDSS >6, OR=2.06). Additionally, we observed lower CSF cell counts (6.68/µl ± 1.37/µl) and lower total CSF protein (412 mg/l ± 18.25 mg/l) of patients who responded to ICT compared to patients who did not (p < 0.05). In the control group no significant differences were revealed. Furthermore analyses of our data revealed patients belonging to the improving group reach an EDSS of 6 after ICT-initiation less often than patients of the active group (after 13 years 39.8% in the improving group, 67.8% in the active group). Conclusion Our study implies two relevant messages: i) it confirms previous observational data on safety and efficacy of ICT as a symptomatic therapy in disease progression in MS; ii) disease onset, EDSS, CSF cell count and total protein may serve as predictive markers for therapy response.